2022
DOI: 10.4269/ajtmh.21-0801
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem Inflammatory Syndrome in Children: Follow-Up of a Cohort from North India

Abstract: Multisystem inflammatory syndrome in children (MIC-S) is a hyperinflammatory manifestation of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. Information on the long-term outcome of MIS-C is limited. This study was conducted to describe the long-term outcome of MIS-C from a tertiary care center in North India. Children admitted with MIS-C from September 2020 to January 2021 were followed up after discharge until June 2021. The details during the acute phase (clinical features, investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…We synthesized outcomes at 3 months from 2 studies [ 27 , 31 ] which explicitly included a follow-up at 3 months and 3 studies [ 17 , 20 , 30 ] which reported data at 100–105 days. We also synthesized outcomes at 6 months from 7 studies [ 16 19 , 28 , 29 , 31 ] which included data at 6 months or 180 days follow-up. A summary of the risk of bias assessment for the prevalence studies for each retrospective cohort study is shown in Supplementary Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…We synthesized outcomes at 3 months from 2 studies [ 27 , 31 ] which explicitly included a follow-up at 3 months and 3 studies [ 17 , 20 , 30 ] which reported data at 100–105 days. We also synthesized outcomes at 6 months from 7 studies [ 16 19 , 28 , 29 , 31 ] which included data at 6 months or 180 days follow-up. A summary of the risk of bias assessment for the prevalence studies for each retrospective cohort study is shown in Supplementary Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The cardiovascular system is one of the main systems involved and it is the major determinant of the acute management and prognosis. Many reports documented a good short-term outcome, but little is known about medium- and long-term follow-ups, and to date, there is only one pediatric paper reporting 3–6-month outcomes, although without insight into the cardiologic aspects [ 31 ]. According to the available literature, the LVEF evaluated by a traditional echocardiogram tends to normalize within 7–10 days after acute treatment.…”
Section: Discussionmentioning
confidence: 99%
“…13 Two Indian studies from northern and eastern India showed the median age to be 6 years and 7 years respectively. 14,15 One study from Kerala found the mean age to be 6.2 years. We may infer from the above that MIS-C is a disorder of children aged more than five years, in contrast to the KD where children of age less than 5 years are mostly affected.…”
Section: Discussionmentioning
confidence: 99%
“…Only few studies found girls to be affected more. 2,3,8,[13][14][15][16][17] Most of the cases recovered. Only 4 (6%) patients died in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation